Kaija Hedman: capstone - Hedman, Kaija, artist (Colorado State University. Libraries, 2021)
The artist's statement: What conditions make a perfect snowflake? This was the question that drove Wilson Bentley, an American Meteorologist, to find what condition makes a perfect snowflake. I came across Bentley's work while researching macro photography and fell in love with his approach to capturing ice. The way Bentley documents snowflakes and the fragile delicate details that are described within the photographs energized me to do my own study of ice. Creating, abstracted ice drives my photography and enlivens nature. What I find fascinating about making ice images is how indefinite these images can be. With these images, I can activate people's imaginations and emotions. My images can take people to a distinct world, where they may feel different emotions like anger, chaos, and/or a sense of nostalgia. The images themselves reveal my technique of taking images. The images displayed a sense of electrical energy that is chaotic and has a quite beautiful form. They hold my vision of photography, that it can be imaginative and frees the mind to react instead of me being proscriptive. I want to open people's eyes that there is beauty all around them and can be something as simple as ice. As I concluded my time at Colorado State University, my ice images are the start to my lifelong portfolio. I, thematically, like to pull at the idea of people stopping and smelling the roses. Seeing the ice specifically continue to hold other people's gazes. Ice has so many uses like keeping your drink cold, being a dangerous element in the winter, or a part of frozen history. As I continue on this journey I hope that I can travel to winter wonderlands and capture their unique ice structures.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photo image making